Changes in Physical Fitness among High Grade Schoolgirls (Baltic Journal of Sport and Health Sciences, 2011)
Research background and hypothesis. During the last five years Lithuanian long-term research related to the peculiarities of changes  in  physical fitness among 10-12 th -grade  schoolgirls has  not  been  found.  Other research in Lithuania showed negative tendencies of physical fitness changes of Lithuanian schoolchildren and prevailing sedentary lifestyle.Research aim was to determine peculiarities of change results in physical fitness among Kaunas schoolgirls (10–12 th  grades).Research methods. The present research included 10 th -grade schoolgirls (n = 244) of Kaunas city who were at school during the research and were able to perform the necessary Eurofit tests: 10  × 5 m Shuttle run, Standing Broad Jump, Sit ups in 30 seconds, 20 m endurance Shuttle run.Research  results.  Changes in results of Eurofit tests performed from 10 th  grade autumn to 12 th  grade spring were different. Results of girls (10–12 th -grade) in 10 × 5 m shuttle run test did not change (p > 0.05). Results of standing broad jump improved significantly in Grade 11 (p  < 0.05). Results in 20 m endurance shuttle run test improved in Grade 12 (p < 0.05). Results in Sit ups in 30 seconds test improved in spring. Significant differences were found between 10 and 12 th -grade schoolgirls spring Sit ups in 30 seconds test results, and 10 and 11 th -grade autumn results.Discussion and conclusions. Comparison of physical fitness of 10 and 12 th -grade girls showed that it improved only in 20 m endurance shuttle run, in the 11 th  grade explosive strength of schoolgirls significantly improved.Keywords: changes in physical fitness, Eurofit tests, physical characteristics.